QUALITY MANAGEMENT MODEL OF PUBLIC COLLEGES AND UNIVERSITIES UNDER GUANGDONG PROVINCE - Fengjin, Liang; Chaisirithanya, Kamolmal (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were (1) to propose the quality management model of public colleges and universities under Guangdong Province; (2) to verify result of quality management model of public colleges and universities under Guangdong Province with empirical data. This research was a mixed research method, including quantitative research and qualitative research. The total population was 46,311, and a total of 480 samples were obtained by stratified random sampling technique. The key informants were principals, vice principals and management experts of public universities in Guangdong Province, obtained by purposive sampling technique, a total of 13 experts. Management experts have worked in universities for more than 10 years. The instruments used for data collection were semi-structured interviews and a five-point rating scale. Data analysis was performed by using statistical software, analyzing frequency, percentage, Standard Deviation, and data were tested using Confirmatory Factor Analysis. The results showed that: (1) the quality management model consisted of nine components: leadership and decision-making, teaching management, logistics management, administrative power and academic power, external resources, school satisfaction, teacher development and talent training, students’ professional knowledge and skills. Teaching quality and scientific research results; and (2) the quality management model of public colleges and universities under Guangdong Province was fit well.